L'Université Interculturelle des Nations et Peuples Autochtones Amawtay Wasi. L'éducation supérieure autochtone peut-elle contribuer à la décolonisation de la société en Équateur ? - Marie-Ève (Les éditions de la Maison des sciences de l'Homme, 2016)
The Intercultural University of Indigenous Nations and Peoples, Amawtay Wasi (House of Wisdom in Kichwa) was officially launched in 2004, following the indigenous struggles of the 90s in Ecuador. At the time, the Charter of Rights of Indigenous Peoples of the United Nations had not yet been ratified, and Ecuador had not yet adopted its new constitution, which recognizes the intercultural nature of Ecuadorian society, the plurinational state, and the collective rights of the different communities, peoples and nationalities of Ecuador. Despite these constitutional and international advances in terms of the recognition of Indigenous Peoples' rights, on the eve of celebrating its 10 years, and after a long and conflicted evaluation process begun in 2009, the university Amawtay Wasi saw its activities officially and indefinitely suspended by the Higher Education Council (CES) in November 2013. How is it possible to explain that situation, in an international and national context that is supposed to increasingly recognize Indigenous self-determination right? What role does Indigenous higher education plays in the decolonization of Ecuadorian society and Nation-State, which both emerged from the European colonialism in the Americas? After more than a year of that forced closure, what strategies the Ecuadorian indigenous organizations are adopting to continue the project of intercultural higher education and of knowledge decolonization? What strategies can Ecuadorian Indigenous organizations implement, in education, and according to what sovereignty, for what decolonization, for what nation(s)? This article attempts to answer these questions based on the Amawtay Wasi's trajectory until its closure in 2013, based on an analysis of the tensions between its political and epistemological projects and those of the actual government, in relation to its "citizen revolution".